English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Evaluate. 2m-5n/n+3p if m=-2, n=4 and p= -1

2006-11-30 11:26:02 · 6 answers · asked by lovely_ladyallday 1 in Science & Mathematics Mathematics

6 answers

4(4)+2x7-(5x4-15)
4x4
16+2x7-(5x4-15)
2x7
16+14-(5x4-15)
5x4-15
16+14-5
16+14
30-5
25=answer

(b)-2bc+c(c)
-2b^2c^3=answer

2x-2-5x4/4+3x-1
-4-20/4+-3
-4-5+-3
-2=answer

2006-11-30 11:36:20 · answer #1 · answered by AYBZ 2 · 0 0

A. Provided that in the first equation, 2x7 and 5x4 mean two times x to the 7th power and five times x to the 4th power, I come out with the answer 31+ 2x7-5x4 after simplification:
16 + 2x7 -5x4 + 15 (combine 16 and 15 via addition; the other two terms cannot be added together because the exponents of x are different.

31 + 2x7 - 5x4

IF 2x7 and 5x4 mean multiplication in your equation, then complete the problem by multiplying:
31 + 14 -20 = 25



B. (3)-2(3)(-2) + -2(-2) =
(3) - (-12) + 4 =
3 + 12 + 4 = 19

IF the problem means (3) times -2(3)(-2) and not (3) minus 2(3)(-2) then multiply the terms instead of subtracting to get:

(3)(12) + 4 = 40


C. 2(-2) -5(4)/ 4+3(-1)
-4 - 20/ 4-3
-24/1 =
-24

The important thing is to understand the concepts. You will need to know algebra to do every other math that comes after it. People before now never had the option of coming to "Answers" to get their homework done. It scares me to think we may be contributing to the ignorance of the future work force by doing their homework.

2006-11-30 11:45:03 · answer #2 · answered by Empress Sky 2 · 0 0

Evaluate.
= 4(4)+2x7-(5x4-15)
= 4(4)+2x7-(20 -15)
= 4(4)+2x7- 5
= 16 + 14 - 5
= 25

(b)-2bc+c(c)
Put in the given values.
(b)-2bc+c(c)
(3)(-2)(3)(-2)+(-2)(-2)
36 + 4
40

Evaluate:
2m-5n / n+3p
Put in the values.
2(-2) -5(4) / (4) + 3(-1)
-4 - 20 / 4 - 3
- 24 / 1
-24

2006-11-30 11:44:43 · answer #3 · answered by Brenmore 5 · 0 0

keep in ideas the order of operations Please Excuse My pricey Aunt Sally first shall we plug contained in the variables 3^2 - (2 * 3 * -2) + -2^2 do the parenthesis first i opt for to do the multiplication from left to proper because its more straightforward -2 * 3 = 6 * -2 = 12 you presently have 3^2 + 12 + -2^2 now do exponents 3^2 = 3 * 3 = 9 -2^2 = -2 * -2 = 4 you presently have 9 + 12 + 4 i imagine you may take it from the following.

2016-11-28 02:36:32 · answer #4 · answered by ? 4 · 0 0

-2

2006-11-30 11:34:27 · answer #5 · answered by DeltaLimaDelta 2 · 0 0

just plug in the ******' numbers and do your own homework

2006-11-30 11:33:01 · answer #6 · answered by Pal G 2 · 0 1

fedest.com, questions and answers